Relationship of Psychosocial Factors towards Medication Adherence among Hypertension Patients in A Tertiary Hospital - Karim, Jalina; Ramli, Hazwani; Mohd Razi, Siti Zuraida; Hassan, Nor Haty (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Hypertension is one of the invisible diseases causing heart failure and stroke, and responsible for death. This study aimed to determine the level of medication adherence and psychosocial factors among patients with hypertension, relationship between socio demographic and medication adherence, and relationship between psychosocial factors and medication adherence among patients with hypertension. MATERIALS AND METHODS: A cross-sectional descriptive study was performed at the Primary Health Clinic and Medical Clinic in one of the tertiary hospitals. There were 123 patients with hypertension who volunteered to participate using a validated adapted and modified questionnaire to assess the compliance and psychosocial factors. The data collected was analysed using IBM SPSS Statistics version 23. RESULTS: A hundred and twenty respondents were adherents to medication (97.6%) while respondents with non-adherence to medication were 3 (2.4%) with a mean adherence score of 42.2764 with SD ± 2.67134. Some of the psychosocial variables had good understanding, good emotional state, positive attitude, higher motivation, higher perception of severity, lower perception of susceptibility and less barrier to compliance. Emotional state was the only thing reported for the psychosocial factors as being statistically significant. The level of emotional state was found statistically significant differences with scores p=0.008 (p< 0.05). CONCLUSION: The level of medication adherence was good which reflected the patients’ compliance towards medication taking. This study showed a good medication adherence and compliance among hypertension patients.